Synergetic effect of testosterone and phophodiesterase-5 inhibitors in hypogonadal men with erectile dysfunction: A systematic review - Alhathal, Naif (Canadian Medical Association, 2012)
Testosterone deficiency seems to impair the clinical response to phophodiesterase-5 (PDE-5) inhibitors in patients with erectile dysfunction (ED). In hypogonadal men, testosterone repletion was associated with enhanced sexual function in patients who failed initial treatment with sildenafil or tadalafil. We conducted a systematic review of studies that evaluated combination therapy of testosterone and PDE-5 inhibitors in patients with ED and low, low-normal testosterone levels who failed monotherapy. The studies we examine are heterogeneous with several methodological drawbacks and that, overall, the addition of testosterone to PDE-5 inhibitors might benefit patients with ED associated with testosterone <300 ng/dL (10.4 nmol/L) who failed monotherapy. Further studies, with a randomized placebo-controlled and double blind design, are needed to describe the appropriate target patient group, testosterone cut-off and to define the optimal dose and duration of combination therapy.